Barriers to accessibility of medicines for hyperlipidemia in low- and middle-income countries. - Chaoyang Li; Garrison Spencer; Muhammad Jami Husain; Rachel Nugent; Deon Auzenne; Deliana Kostova; Patricia Richter (Public Library of Science (PLoS), 2024)
Despite the high burden of hyperlipidemia and the effectiveness of treatment, evidence suggests that the accessibility of hyperlipidemia medicines can be low in many low- and middle-income countries (LMICs). The aim of this study was to identify common barriers to the accessibility of medicines for hyperlipidemia in LMICs. A multimethod analysis and multiple data sources were used to assess the accessibility and barriers of medicines for hyperlipidemia in selected LMICs. The overall median availability of statins for hyperlipidemia in public facilities was 0% and 5.4%, for originators and generics, respectively. In private facilities, median availability was 13.3% and 35.9%, for originators and generics, respectively. Statin availability was lowest in Africa and South-East Asia. Private facilities generally had higher availability than public facilities. Statins are less affordable in lower-income countries, costing around 6 days' wages per month. Originator statins are less affordable than generics in countries of all income-levels. The median cost for statin medications per month ranges from a low of $1 in Kenya to a high of $62 in Mexico, with most countries having a median monthly cost between $3.6 and $17.0. The key informant interviews suggested that accessibility to hyperlipidemia medicines in LMICs faces barriers in multiple dimensions of health systems. The availability and affordability of statins are generally low in LMICs. Several steps could be implemented to improve the accessibility of hyperlipidemia medicines, including private sector engagement, physician education, investment in technology, and enhancement of health systems.